The reaction of N-dichlorophosphoryl-P-trichlorophosphazene with alkyl Grignard reagents - Aslan, F; Ozturk, AI; Arslan, M (Wiley, 2003)
The reactions of N-dichlorophosphoryl-P-trichlorophosphazene Cl3P=N-P(O)Cl-2 (1) with benzylmagnesium bromide, 2-phenylethylmagnesium bromide, trimethylsilylmethylmagnesium chloride, n-butylmagnesium bromide, cyclopentylmagnesium bromide, cyclopentylmagnesium bromide, tert-butylmagnesium bromide, iso-propylmagnesium bromide, and ethylmagnesium bromide were studied. Tri- and pentaalkyl phosphazenes were obtained in very poor yield from trimethylsilylmethylmagnesium chloride and cyclohexylmagnesium bromide, respectively. Tri-alkylphosphoryl compounds formed from benzyl-, 2-phenylethyl-, and n-butylmagnesium bromide. No phosphorus compound could be isolated from the reaction of I with t-butyl-, cyclopentyl-, iso-propyl-, and ethylmagnesium bromide. (C) 2003 Wiley Periodicals, Inc.
Keywords: Phosphorus-Nitrogen Compounds; Chain Linear Phosphazenes; Trimeric Phosphonitrilic Fluoride; Block-Copolymers; Side-Groups; Crystal-Structure; Aminolysis; Chemistry; Polymerization; Trichloride